2023
DOI: 10.1175/aies-d-22-0094.1
|View full text |Cite
|
Sign up to set email alerts
|

Using Neural Networks to Learn the Jet Stream Forced Response from Natural Variability

Abstract: Two distinct features of anthropogenic climate change, warming in the tropical upper troposphere and warming at the Arctic surface, have competing effects on the mid-latitude jet stream’s latitudinal position, often referred to as a “tug-of-war”. Studies that investigate the jet’s response to these thermal forcings show that it is sensitive to model type, season, initial atmospheric conditions, and the shape and magnitude of the forcing. Much of this past work focuses on studying a simulation’s response to ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Following recent work showing that ML methods can effectively isolate internally generated and externally forced trends (Barnes et al., 2019; Connolly et al., 2023; Gordon & Barnes, 2022; Po‐Chedley et al., 2022), we create ML algorithms to isolate these trend contributions in observed surface air temperature during the 43‐year period from 1980 to 2022 over both the Arctic and globe. To do this, we create a training data set based on 10 CMIP6 models, of which each have at least 10 ensemble members (Table S1 in Supporting Information ).…”
Section: Methodsmentioning
confidence: 99%
“…Following recent work showing that ML methods can effectively isolate internally generated and externally forced trends (Barnes et al., 2019; Connolly et al., 2023; Gordon & Barnes, 2022; Po‐Chedley et al., 2022), we create ML algorithms to isolate these trend contributions in observed surface air temperature during the 43‐year period from 1980 to 2022 over both the Arctic and globe. To do this, we create a training data set based on 10 CMIP6 models, of which each have at least 10 ensemble members (Table S1 in Supporting Information ).…”
Section: Methodsmentioning
confidence: 99%
“…Following recent work showing that ML methods can effectively isolate internally generated and externally forced trends (Barnes et al, 2019;Connolly et al, 2023;Gordon & Barnes, 2022;Po-Chedley et al, 2022), we create ML algorithms to isolate these trend contributions in observed surface air temperature during the 43-year period from 1980 to 2022 over both the Arctic and globe. To do this, we create a training data set based on 10 CMIP6 models, of which each have at least 10 ensemble members (Table S1 in Supporting Information S1).…”
Section: Methodsmentioning
confidence: 99%
“…As each SSW manifests a predominant spatial pattern in the stratosphere (either displacement-type or split-type structure), deep learning models, especially those that are salient in extracting features from two-dimensional images, could offer a new opportunity to examine SSW morphology. Convolutional neural networks (CNNs) are a deep learning technique developed to tackle such image recognition tasks and have been widely used in multiple earth science problems to extract key spatial structures (Ham et al 2019, Connolly et al 2023. In addition, variational auto-encoders (VAEs; Kingma and Welling 2013), a typical type of generative deep learning model, have been extensively utilized in retrieving non-linear relationships in geoscience data (Vuyyuru et al 2021, Lopez-Alvis et al 2022, Tsekhmistrenko et al 2022.…”
Section: Introductionmentioning
confidence: 99%